Gingival health in relation to salivary vitamin C and total protein among dental students - Nada J Radhi (College of Dentistry/ University of Baghdad, 2014)
Background: The protective roles of vitamin C and total proteins in gingival inflammation were reported by several studies. The aim of this study was to measure the concentration of salivary vitamin C, total protein and their relation to gingival health among dental students. Materials and methods: The sample consisted of 67 dental students (33 males and 34 females) from College of Dentistry, University of Baghdad. Sillness and Löe (1964) was used for recording of dental plaque, while the gingival index (GI) was measured according to Löe and Sillness criteria (1963). Stimulated salivary samples were collected and chemically analyzed in Poisoning Center/Surgical Specialty Hospital by using colorimetric method to measure the salivary vitamin C and total protein. SPSS version 18 was used for analyzing data. Results: A higher percentage of dental students were found with mild type of gingivitis. Higher mean value of salivary vitamin C was reported among dental students with mild type of gingival index compared to those with moderate type, while the opposite picture was noticed for total protein, differences were statistically significant (P< 0.05). Conclusion: Significant associations between salivary vitamin C, total protein and gingivitis were found in the present study. The protective rule of salivary vitamin C and total protein may offer a route to improve oral healthcare.